Komunikasi Inovasi dalam Pemanfaatan Lahan Pekarangan Komunitas Petani untuk Mewujudkan Kemandirian Pangan di Era Digital - Leonard Dharmawan; Adi Firmansyah; Tri Susanto (Jurnal Komunikasi Pembangunan, 2019)
Communication innovation is a way of conveying the discovery of new ideas to the community for a social change to occur. Utilization of land is an innovation for rural areas today to achieve food independence. The objectives of this study include: 1) Knowing the adoption process for innovative land use for food resources in Doudo Village. 2) Understand how the community optimizes the yard in Doudo Village. 3) Knowing the digital media that people use in marketing their products. The study was conducted on the people of Doudo Village, Gresik Regency, East Java. From July to October 2017. This study uses descriptive and exploratory methods. Primary data taken by key informants and sources related to activities. The results show that the adoption process of innovation is initiated by change agents by mapping community leaders who have credibility, so that they can influence the community. Comparative and observability advantages are the dominant factors that influence the use of land. The types of plants planted include a) family medicinal plants, b) ornamental plants, c) protective plants, d) vegetables, and e) shade plants. The yield from planting is added value so that it can be sold to increase income. Finally, land use is carried out by community leaders and distributed to other communities.